Malarstwo ikonowe tradycji bizantyjskiej - Koprowski, Piotr (Studia Europaea Gnesnensia, 2015)
The article seeks to reflect upon the manner of perceiving reality (the so-called reversed perspective) associated with the Byzantine tradition of icon painting which was in evidence in the Ruthenian and Russian cultural circle from the 12th to the first half of the 17th century.